2010
DOI: 10.1891/1078-4535.16.4.155
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Learning: Fostering a Culture of Curiosity

Abstract: Lifelong learning contributes to the development of knowledge and skill in nursing. A focus on continuous learning is necessary to remain current on trends, practices, and the newest treatments in the field of nursing. Creation of a culture where educational growth is supported and promoted is vital to advancement of the nursing profession. Nurses' satisfaction with their professional role can be further enhanced by demonstrated expertise through lifelong learning. Expertise in nursing is solidly founded on ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In other words, students demonstrating learner independence are more likely to also have intellectual curiosity. Similar findings were reported in Eason's (2010) study, which examined ways to foster intellectual curiosity and lifelong learning in nurses. Eason also found that environments and cultures that support learning ignite intellectual curiosity.…”
Section: Predictors Of Self-directed Learning Readiness Of Nursing Stsupporting
confidence: 87%
“…In other words, students demonstrating learner independence are more likely to also have intellectual curiosity. Similar findings were reported in Eason's (2010) study, which examined ways to foster intellectual curiosity and lifelong learning in nurses. Eason also found that environments and cultures that support learning ignite intellectual curiosity.…”
Section: Predictors Of Self-directed Learning Readiness Of Nursing Stsupporting
confidence: 87%
“…We recognize that ongoing training and development is part of a lifelong learning process, and, in keeping with Eason (2010), view educational curiosity not only as a professional necessity but a beneficial trait for accomplishment, growth and fulfillment. By cultivating curiosity, the JNC model helps motivate students to close gaps in their knowledge while encouraging them to adopt the social group work method as part of their professional identity.…”
Section: Discussionmentioning
confidence: 84%
“…Writing is central to higher education, and nursing studies at undergraduate level and beyond require critical analysis demonstrated in writing (Duffy et al, 2009). As well as writing skills, success in nursing education requires information literacy (Tarrant et al, 2008) and the development of evidence-based nursing practice (Eason, 2010).…”
Section: Writing As a Barrier To Learningmentioning
confidence: 99%
“…A significant development over the last two decades is the expectation that nurses become independent lifelong learners (Eason, 2010;Jarvis, 1986;Kedge and Appleby, 2009;Roberts, 2011), which entails the continuous building of skills and knowledge throughout life by formal, non-formal or informal learning (European Commission, 2001). To be effective, it requires a deep approach to learning (Cowan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%